Valores organizacionais: uma análise no contexto educacional - Casagrande, Renato José (2001)
This research¿s main goal was to analyze the existing relationship between both environmental and organizational values from three State Schools located in the city of Curitiba. These are: Protásio de Carvalho School, Guaíra School and Rio Branco School. At a theoretical empirical reference, an environmental approach has been performed, followed by aspects regarding organizational values, including the discussion on the theme of organizational culture, and, finally, a study on the prevalent values in public educational institutions. The method that best features this research is a comparative case report, with the use of multiple sources of evidence. Secondary data in order to identify the environmental values has been obtained through references of two of the most important newspapers in the State of Paraná, reports published by the State¿s Secretary of Education, publications from the State¿s Teachers Union and through the Educational Legislation in both Federal and State levels. The organizational values have been identified from primary data obtained through semi-structured interviews, performed with the School Principals and through questionnaires distributed to the School Principals and Teachers. The analysis over this data has been carried out in a descriptive-qualitative way by using both documentary and content analysis techniques. The database revealed that there are a few consistencies between environmental and organizational values, in a way that certain values identified in society and in the Government are, several times, more congruent with the values identified in the group of School Principals, whereas the values identified in the Teacher¿s Union have a higher consistency with the prevalent values in the group of teachers. At schools, mainly in the group of teachers, there¿s a noticeable refraction towards actions promoted by the government, and a certain skepticism towards actions promoted by the Teacher¿s Union. The student¿s education is given a higher value than one¿s cognitive education, in the work atmosphere as much as in the organizations; the Society has been gradually taking the responsibility regarding public education, with the support of school boards, teachers, and even of the Government, at a time when teachers, unlike the Society and the Government, appear to give very little value to their own profession.